ASSESSING CONTRIBUTORY FACTORS IN POTENTIAL HAZARD NATURAL GAS PIPELINE FAILURE - Ahmad Hasnan; Zefry Darmawan; Ade Iskandar; Aswin Aswin; Diar Azzis Septian (JEMIS (Journal of Engineering & Management in Industrial System), 2023)
Increased energy demand in Indonesia is accompanied by increasing demand for natural gas, where in the next 50 years natural gas is predicted to be the number one energy source in Indonesia, pipeline is the cheapest way to distribute natural gas, in this way, length of pipeline infrastructure will increase year by year. it is still very much needed by both the household, industry, and power plants. The longer the pipeline, the risk of pipeline failure also increases, it is necessary to understand what factors have the most influence on pipeline failure, the method used is to create a factor matrix from a modified Muhlbauer, MICMAC is used to test the strength of the relationship between significant factors causing the potential hazard of pipeline failure. based on their influences and dependencies. The value of the dependency relationship between factors is determined from discussions with several pipeline experts in Indonesia, who work in related fields, the result is that there are three main factors that contribute major potential hazards, without being influenced by other factors, that is determining safety factors in the design process, depth pipeline and the existence of SOP in the pipeline system. One factor, namely depth, can be eliminated because there are government regulations requiring natural gas pipelines to be buried in the ground at a certain depth.